Retrospective Study: Malassezia Folliculitis Profile - Putri Intan Primasari; Evy Ervianti (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Malassezia folliculitis (MF) is a chronic infectious disease of pilosebaceous follicles caused by Malassezia sp. Clinical features of MF include erythematous papules and itchy perifollicular pustules, especially on the upper body, neck, upper arms, and face. The disease is usually reported on adolescents. Objective: To evaluate the profile of MF patients in four years (2014-2017) period in the Mycology Division of Dermatovenerology Outpatient Clinic of Dr. Soetomo General Academic Hospital Surabaya. Methods: This study was a retrospective study to examine the medical records of MF patients in the Mycology Division of Dermatovenerology Outpatient Clinic General Academic Hospital Dr. Soetomo Surabaya from January 2014 to December 2017. Results: The number of new MF patient visits during 2014-2017 was 196 patients, and the average annual visit was 55 patients in 2014, 49 patients in 2015, 65 patients in 2016, and 27 patients in 2017. The majority of patients were males, were aged 15-24 years old. The chief complaint was reddish papules accompanied by moderate itching in the predilection area and most often found in the upper body. The Wood's lamp examination revealed greenish-yellow color, and 20% KOH examination showed spores. Most systemic therapies was ketoconazole and tretinoin 0.05% cream for topical therapy. Conclusions: There was a decrease in the number of MF patients. The diagnoses of MF were based on history taking, physical examination, 20% KOH, and Wood's lamp.